Pengaruh Pengalaman dan Kepuasan Pelanggan terhadap Keputusan Pembelian Cat Tembok Merek X - Dameria, Yanti; Ericka, Anastacia; Gamelawati, Hanes Siti Praselia; Winarto, Jacinta (Jurnal Informatika Ekonomi Bisnis, 2025)
This abstract aims to determine the extent to which customer experience and customer satisfaction influence the purchasing decision of wall paint X. A quantitative method was employed, using surveys distributed via questionnaires to consumers in Bandung district and city who have previously used brand X wall paint. This method was selected to objectively examine the relationship between variables in this research using numerical data suitable for statistical analysis. The research falls under the causal-explanatory category, which aims to explain the cause-and-effect relationship between the variables of customer experience X1, customer satisfaction X2, and purchasing decision Y. The sampling technique used was purposive sampling, with respondents selected based on specific criteria, namely those who have prior experience using the wall paint product of brand X. Primary data were collected directly from respondents through structured questionnaires as the main data collection tool. The results show that customer experience has a significant influence on purchasing decisions. Likewise, customer satisfaction significantly affects product purchasing decisions. Moreover, the analysis reveals that both customer experience and satisfaction together contribute 80.8% to the variation in purchasing decisions. Therefore, it is recommended that the company improve the quality of customer experience and satisfaction to strengthen its marketing strategy and customer loyalty in a highly competitive market.